2021
DOI: 10.1155/2021/1776567
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Venous Thromboembolism and Periodontal Diseases: A Bioinformatics Analysis

Abstract: Background. This current study applied bioinformatics analysis to reveal the crosstalk between venous thromboembolism (VTE) and periodontitis, as well as the potential role of immune-related genes in this context. Methods. Expression data were downloaded from the GEO database. Blood samples from venous thromboembolism (VTE) were used (GSE19151), while for periodontal disease, we used gingival tissue samples (GSE10334, GSE16134, and GSE23586). After batch correction, we used “limma” packages of R language for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Three possible mechanisms of interaction between VTE and periodontitis include (1) invasion of vascular system by periodontal pathogen, (2) effect of periodontitis-induced inflammation on platelet function and risk of thrombosis, and (3) effect of shared risk factors including diabetes and smoking. [ 40 ] Hence, periodontal disease can be suggested to be a modifiable risk factor associated with thromboembolic disease. Further controlled clinical studies are needed to validate specific mechanism underlying periodontal disease and thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…Three possible mechanisms of interaction between VTE and periodontitis include (1) invasion of vascular system by periodontal pathogen, (2) effect of periodontitis-induced inflammation on platelet function and risk of thrombosis, and (3) effect of shared risk factors including diabetes and smoking. [ 40 ] Hence, periodontal disease can be suggested to be a modifiable risk factor associated with thromboembolic disease. Further controlled clinical studies are needed to validate specific mechanism underlying periodontal disease and thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the deletion of SAMSN1 significantly affected multiple cell types contributing to MM development 14 . In addition, recent research demonstrated that SAMSN1 is a biomarker crosstalk gene between periodontitis and venous thromboembolism 17 . Another study has found that platelet gene expression profiling can detect the early signal of impending acute myocardial infarction (AMI) before the occurrence of infarction, and SAMSN1 is one of the DEGs in platelet gene expression profiling 18 ; meanwhile, SAMSN1 is reported as a gene associated with coronary atherosclerosis and B‐cell activation 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Target genes associated with periodontitis were searched using the GeneCards platform (https://www.genecards.org/)[18],, OMIM platform (https://www.omim.org/) [19], and DrugBank platform (https://www.drugbank.ca/) [20]. Two datasets, GSE10334 and GSE16134[8, 21,22], were obtained by searching the GEO database (https://www.ncbi.nlm.nih.gov/geo/) for periodontitis-related datasets using the keyword "periodontitis". The samples in both datasets were obtained from gingival tissue, with the experimental group consisting of samples from individuals with periodontitis and the control group consisting of samples from individuals with healthy gingiva.…”
Section: Predicting the Targets Of Astragalus For Periodontitis Treat...mentioning
confidence: 99%